Preschoolers have better long‐term memory for rhyming text than adults. Issue 3 (21st February 2016) - Király, Ildikó; Takács, Szilvia; Kaldy, Zsuzsa; Blaser, Erik
Abstract: The dominant view of children's memory is that it is slow to develop and is inferior to adults'. Here we pitted 4‐year‐old children against adults in a test of verbatim recall of verbal material. Parents read a novel rhyming verse (and an integrated word list) as their child's bedtime story on ten consecutive days. A group of young adults listened to the verse, matching the exposure of children. All participants subsequently performed a free‐recall of the verse, verbatim. (Parents and young adults knew they would be tested; children did not.) Four‐year‐olds significantly outperformed both their parents and the young adults. There were no significant differences in the ability to recall the gist of the verse, nor the integrated word list, allaying concerns about differences in engagement or motivation. Verbatim recall of verse is a skill amenable to practice, and children, we argue, by virtue of the prominence of verse in their culture and their reliance on oral transmission, have honed this skill to exceed adults'. Abstract : Parents read a novel rhyming verse as their child's bedtime story on ten consecutive days. A group of young adults listened to the verse, matching the exposure of children. All participants subsequently performed a free‐recall of the verse, verbatim. Four‐year‐olds outperformed both groups of adults, with free‐recall of nearly twice as many correct words of the verse, and far fewer errors. Children's memory for verbatim recall is excellent.